Reduction of hyperglycemia in STZ-induced diabetic mice by prophylactic treatment with heat-killed Mycobacterium aurum: possible effects on glucose utilization, mitochondrial uncoupling, and oxidative stress in liver and skeletal muscle - Abdallah, Farid; Bazzi, Samer; Akle, Charles; Bahr, Georges M.; Echtay, Karim S. (Frontiers in Endocrinology, 2024)
Background: Besides conventional treatment and modifications in physical activity and diet, alternative strategies have been investigated to manage, prevent, or delay diabetes in humans. In this regard, one strategy has relied on the immunomodulatory properties of mycobacteria whereby Bacillus Calmette-Guerin (BCG), an attenuated live strain of Mycobacterium bovis, has been shown to improve glycemic control in diabetic patients and to alleviate hyperglycemia in selected murine models of diabetes. A novel heat-killed (HK) whole cell preparation of Mycobacterium aurum (M. aurum) is currently under development as a potential food supplement; nevertheless, its potential bioactivity remains largely unknown. Thus, the present study investigated the potential prophylactic anti-diabetic effects of HK M. aurum in streptozotocin (STZ)-induced diabetic mice.Methods: Mice were divided into 3 groups: the STZ-induced diabetic group was injected with a single intraperitoneal high dose of STZ, the HK M. aurum-treated diabetic group was prophylactically treated with 3 doses of HK M. aurum 6 weeks pre-STZ injection and the control non-diabetic group was given 3 intradermal injections of borate-buffered saline and an intraperitoneal injection of citrate buffer. Liver lactate dehydrogenase (LDH), uncoupling protein 2 (UCP2) and glucose transporter 2 (GLUT2) and skeletal muscle LDH, UCP3 and GLUT4 protein expression levels in different mouse groups were determined by western blot.Our results indicated that HK M. aurum did not cause any significant changes in glycemic levels of normal non-diabetic mice. Prophylactic administration of three doses of HK M. aurum to diabetic mice resulted in a significant reduction in their blood glucose levels when compared to control diabetic mice. Prophylactic treatment of diabetic mice with HK M. aurum significantly restored their disturbed protein expression levels of liver UCP2 and LDH as well as of skeletal muscle UCP3. On the other hand, prophylactic treatment of diabetic mice with HK M. aurum had no significant effect on their liver GLUT2 and skeletal muscle GLUT4 and LDH protein expression levels.Our findings provide the first evidence that HK M. aurum possesses a hyperglycemia-lowering capacity and might support its future use as a food supplement for the amelioration of diabetes.